THE ROLE OF FEEDBACK IN THE TEACIDNG AND LEARNING OF WRITING - Aridah Aridah (Celt: A Journal of Culture, English Language Teaching & Literature, 2003)
Feedback, which is not new in the practice of teaching and learning of writing, has become a controversial issue recently. A n important point of debates is whether feedback is necessQl)'. This article aims to discuss the issue offeedback by providing arguments thatfeedback is helpful and language learners do need it. A number of evidences for the use of feedback are provided. In terms of grammatical errors, feedback contributes to improvement in the accuracy of students' writing. On the other hand, feedback on contents provides students with hints for ideas to be developed further and helps stimulate the development of their logical reasoning. This a,.,icle also highlights the issue offeedbackfrom the perspective of the students. An emphasis on the importance offurther research on feedback concludes the discussion in this Ql1ic/e.